On the Importance of Halogen Bonding Interactions in Two X-ray Structures Containing All Four (F, Cl, Br, I) Halogen Atoms - Dmitriy F. Mertsalov; Rosa M. Gomila; Vladimir P. Zaytsev; Mikhail S. Grigoriev; Eugeniya V. Nikitina; Fedor I. Zubkov; Antonio Frontera (Crystals, 2021)
This manuscript reports the synthesis and X-ray characterization of two octahydro-1H-4,6-epoxycyclopenta[c]pyridin-1-one derivatives that contain the four most abundant halogen atoms (Ha) in the structure with the aim of studying the formation of Ha···Ha halogen bonding interactions. The anisotropy of electron density at the heavier halogen atoms provokes the formation of multiple Ha···Ha contacts in the solid state. That is, the heavier Ha-atoms exhibit a region of positive electrostatic potential (σ-hole) along the C–Ha bond and a belt of negative electrostatic potential (σ-lumps) around the atoms. The halogen bonding assemblies in both compounds were analyzed using density functional theory (DFT) calculations, molecular electrostatic potential (MEP) surfaces, the quantum theory of “atom-in-molecules” (QTAIM), the noncovalent interaction plot (NCIplot), and the electron localization function (ELF).